A FORMAÇÃO DO PEDAGOGO NA MODALIDADE EDUCAÇÃO A DISTÂNCIA DA UNIVERSIDADE ESTADUAL DO CENTRO-OESTE (UNICENTRO): DO ASPECTO HISTÓRICO DA EaD À ORGANIZAÇÃO DA PROPOSTA PEDAGÓGICA DO CURSO DE PEDAGOGIA - Oliveira, Vanêssa de Cássia (2021)
The work presents an investigation whose problematic is configured in how the formation of the pedagogue takes place in the Licentiate Degree in Pedagogy at UNICENTRO in the Distance Education modality. The objective of the research is to analyze the Course's curriculum in the Distance Education modality, which breaks down into specific objectives: Contextualize the history of Distance Education internationally and specifically in Brazil; investigate the materialization of Distance Education in Brazilian research; elucidate aspects of public educational policies and public policies for Distance Education in Brazil, considering their legal regulations; analyze the aspect of the organization of the pedagogical proposal of the UNICENTRO Distance Pedagogy Course. For this, we used bibliographical and documentary research of a qualitative nature, under the content analysis of Bardin (1978), within the following internal documents: Current matrix (2010) of the Pedagogy Course in the Distance Education modality at UNICENTRO campus Irati; syllabus (2010) of the Pedagogy Course in the Distance Education modality at UNICENTRO campus Irati; Curriculum Pedagogical Project and its Resolutions: Approval Resolution (2010), Amendment Resolution (2010), Amendment Resolution (2015) and Amendment Resolution (2019); Pedagogical Curriculum Project (PPC) ofthe Pedagogy Course in the face-to-face modality of the State University of the CenterWest UNICENTRO, Irati/PR campus; Pedagogical Curriculum Project (PPC) of the Pedagogy Course in the Distance Education modality at the State University of the Center West UNICENTRO, Irati/PR campus. We use the theoretical-methodological framework of authors who discuss the Pedagogy Course, Libâneo (2001, 2007), and the education of the pedagogue, Cruz (2008), the education of the pedagogue in EaD Leal (2012), about Distance Education , Passos (2018), Vieira (2011), Belloni (2012), on politics, Rizvi and Lingard (2013), EaD public policies, Pimentel (2018), de Bourdieu (2014, 2017) for the discussion on State and field concept. The research is part of the Research Line Educational Policies, History and Organization of Educationand also in the reflections carried out in the State Research Group, Policies and Management in Education/UNICENTRO. The research is structured in sections that address historical, political, normative and legal aspects of Distance Education and the training of pedagogues in this modality. It is concluded that when analyzing the documents, it was found that the training of pedagogues in the Distance Education modality occurs in curricular, normative, legal and teaching standards similar to the on-site course, and that the differentiation is due to methodological aspects of pedagogical practice, which expands the use of Virtual Environment platforms (AVAs) and uses other technological means in conducting classes. It was also possible to show through the internal regulations that the education of pedagogues in EaD goes through a process of specific constitution, which takes place through specific face-to-face moments at the face-to-face support centers. The assessments and their applications are carried out under certain conditions and under certain criteria and theprocess of organizing the Course as a whole is broad and structured, each segment ofthe teaching and learning process has specific features that contribute to allowing students autonomy.